2005
DOI: 10.1073/pnas.0501525102
|View full text |Cite
|
Sign up to set email alerts
|

Molecular recognition of an ADP-ribosylating Clostridium botulinum C3 exoenzyme by RalA GTPase

Abstract: C3 exoenzymes (members of the ADP-ribosyltranferase family) are produced by Clostridium botulinum (C3bot1 and -2), Clostridium limosum (C3lim), Bacillus cereus (C3cer), and Staphylococcus aureus (C3stau1-3). These exoenzymes lack a translocation domain but are known to specifically inactivate Rho GTPases in host target cells. Here, we report the crystal structure of C3bot1 in complex with RalA (a GTPase of the Ras subfamily) and GDP at a resolution of 2.66 Å. RalA is not ADP-ribosylated by C3 exoenzymes but in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 41 publications
0
33
1
Order By: Relevance
“…Another possible explanation for the inhibitory effect is that Ral prevents conformational changes in C3bot, which occur during the ADP-ribosylation. It is noteworthy that the crystal structure of the RAL-C3 complex reported by Acharya and coworkers (Holbourn et al 2005) predicts an interaction of the GTPase with the ARTT loop of C3. However, this model could not be supported by biochemical and mutational data (Pautsch et al 2005).…”
Section: Non-enzymatic Interaction Of C3-like Exoenzymes With Ralmentioning
confidence: 93%
See 1 more Smart Citation
“…Another possible explanation for the inhibitory effect is that Ral prevents conformational changes in C3bot, which occur during the ADP-ribosylation. It is noteworthy that the crystal structure of the RAL-C3 complex reported by Acharya and coworkers (Holbourn et al 2005) predicts an interaction of the GTPase with the ARTT loop of C3. However, this model could not be supported by biochemical and mutational data (Pautsch et al 2005).…”
Section: Non-enzymatic Interaction Of C3-like Exoenzymes With Ralmentioning
confidence: 93%
“…The molecular basis of the C3bot-RalA interaction was recently identified by two groups (Holbourn et al 2005;Pautsch et al 2005). The structure of a stochiometric RalA (GDP)-C3bot complex with an apparent K D value of ∼60 nM was determined by X-ray crystallography (Pautsch et al 2005).…”
Section: Non-enzymatic Interaction Of C3-like Exoenzymes With Ralmentioning
confidence: 99%
“…Holbourn et al (52) and Pautsch et al (53) have reported different structures for the C3-RalA complex; however, the former ␣4-ARTT model is likely to be a crystallographic artifact, based on crystallographic and mutational results (53). The model proposed by Pautsch et al (53) is that the loop between helices ␣3 and ␣4 (C3bot93-C3bot101) inserts into the groove of the switch I and II regions of RalA.…”
Section: Discussionmentioning
confidence: 99%
“…Although the members of this family have homologous enzymatic domains and similar active sites, these toxins ADP ribosylate and therefore, disable a range of cellular targets (Holbourn et al, 2005). Rho family GTPases controls the assembly of both cell-matrix and cell-cell adhesion complexes.…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of these bacterial enzymes has not only made them a valuable tool for elucidating the cellular functions of their targets but has also increased our understanding of protein interactions (Holbourn et al, 2005). Clostridium botulinum is no exception, producing 2 classes of enzymes that have very specefic protein targets, neurotoxin A-G and the ADPribosyltrans-ferases C2, C3 bot 1, and C3 bot 2 (Holbourn et al, 2005). C2 and C3 bot are part of a larger family of ADPribosylating toxins, including diphtheria toxin and cholera toxin, which cleave NAD and transfer ADP-ribose to target proteins.…”
Section: Discussionmentioning
confidence: 99%